Post-Pandemic Measles Resurgence in Indonesia: Longitudinal Evidence of Immunisation Debt Across 34 Provinces, 2018–2024 - Dwiva Wulan Guri; Anggita Rana Sasmita Lestari (Universitas Muhammadiyah Surabaya, 2026)
The COVID-19 pandemic disrupted routine immunisation services globally, creating immunisation debt that may drive measles resurgence. This longitudinal ecological study examined measles outbreak (KLB) frequency and MR1 vaccination coverage across 34–38 Indonesian provinces from 2018 to 2024, divided into pre-pandemic (2018–2019), pandemic (2020–2021), and post-pandemic (2022–2024) phases. Data were extracted from the Profil Kesehatan Indonesia 2018–2024. KLB frequency differed significantly across phases (Kruskal-Wallis H = 32.530, p < 0.001): pandemic-era KLB was suppressed to 6–8 events/year, then rebounded to pre-pandemic levels in 2022–2024 (Mann-Whitney U = 3563.5, p = 0.578) despite lower MR1 coverage, peaking at 137 events in 2023. Negative binomial regression indicated the pandemic phase was associated with an 88.0% reduction in KLB frequency (IRR = 0.120, p < 0.001). Exploratory Spearman correlation between MR1 coverage and KLB frequency was non-significant across all strata (pooled rₛ = +0.089, p = 0.165). Thirty-one high-risk province-year observations were identified across 13 provinces, concentrated in Aceh and Papua. Post-pandemic KLB trends are consistent with the immunisation debt hypothesis. Targeted catch-up vaccination and province-specific strategies for Aceh and Papua are urgently needed.